(untitled) (International Journal of Engineering and Computer Science, 2017)
Vehicle health monitoring in a Developing Nation (VHMDN) is a collection of data relevant to the present and future performance of a vehicle system and its transformation into information to be used to support operational decisions. The ideal was conceived due to the fact that Standard Organization of Nigeria (SON) a body design to regulate the strength of material has not work to expectation in the Country. This paper is design to embraces an integration of sensors, communication technologies, and Artificial intelligence to provide vehicle wide abilities to diagnose problems and recommend solutions as well as to estimate the total remaining life spam of the material. In Africa, the major concentration of Vehicle parts are mainly on fairly used components or parts, which is popularly called “TOKUBO” and these parts life time cannot be quantifier, the idea was based on the fact that new parts are very expensive and can be of lower standard or may be imported from undeveloped Nation. The introduction begins with a brief history of VHM technology development. Recent research has begun to recognize that the VHM problem is fundamentally one of the statistical pattern recognition (SPR) and a paradigm to address such a problem is described in detail herein as it forms the basis for organization of this theme issue